2021
DOI: 10.1038/s41598-021-03343-3
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index but not genetic risk is longitudinally associated with altered structural brain parameters

Abstract: Evidence from previous studies suggests that elevated body mass index (BMI) and genetic risk for obesity is associated with reduced brain volume, particularly in areas of reward-related cognition, e.g. the medial prefrontal cortex (AC-MPFC), the orbitofrontal cortex (OFC), the striatum and the thalamus. However, only few studies examined the interplay between these factors in a joint approach. Moreover, previous findings are based on cross-sectional data. We investigated the longitudinal relationship between i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 57 publications
3
10
0
Order By: Relevance
“…There is established literature supporting the relationship between higher BMI and aspects of MS severity, including cross‐sectional and longitudinal changes in grey matter volumes [34–39]. This is not necessarily an MS‐specific effect, as similar results, particularly between higher BMI and lower grey matter volumes, have been found in people without MS [40–48]. Interestingly, given our finding of a relationship between greater prematurely achieved CVR or higher lipid ratios and worse verbal working memory performance, one previous study of predominantly RRMS found that higher FRS is also associated with poorer CVLT‐II performance [49].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…There is established literature supporting the relationship between higher BMI and aspects of MS severity, including cross‐sectional and longitudinal changes in grey matter volumes [34–39]. This is not necessarily an MS‐specific effect, as similar results, particularly between higher BMI and lower grey matter volumes, have been found in people without MS [40–48]. Interestingly, given our finding of a relationship between greater prematurely achieved CVR or higher lipid ratios and worse verbal working memory performance, one previous study of predominantly RRMS found that higher FRS is also associated with poorer CVLT‐II performance [49].…”
Section: Discussionsupporting
confidence: 72%
“…There is established literature supporting the relationship between higher BMI and aspects of MS severity, including cross-sectional and longitudinal changes in grey matter volumes [34][35][36][37][38][39]. This is not necessarily an MS-specific effect, as similar results, particularly between higher BMI and lower grey matter volumes, have been found in people without MS [40][41][42][43][44][45][46][47][48].…”
Section: Ta B L Ementioning
confidence: 76%
“…Missing data were excluded from analysis (Apolipoprotein ε4[ APOE ε4 ; n = 41], body mass index [BMI; n = 5], physical activity [ n = 122], smoking status [ n = 1], total to high‐density lipoprotein [HDL] cholesterol ratio [ n = 10], anti‐cholesterol medication [ n = 1], prevalent diabetes [ n = 7], cardiovascular disease [CVD; n = 1], adiponectin [ n = 342], CD40 [ n = 18], CRP [ n = 17], 8‐EPI‐isoprostane [ n = 281], fibrinogen [ n = 16], IL‐6 [ n = 18], IL‐18 [ n = 91], intercellular adhesion molecule [ICAM; n = 16], resistin [ n = 335], and TNF‐α [ n = 488]). Confounders were selected based on the published literature (Table S4 in supporting information) 36–42 . Model 1 was adjusted for age, age squared, sex, and the time interval between examination cycle 7 (i.e., baseline FFQ and covariates assessment) and the measurement of MRI outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…To determine if our results remain stable and significant when accounting for potential confounds known to affect brain health, we repeated the aforementioned cross-sectional and longitudinal analyses for reproductive span, menarche, and menopause using additional parameters. More specifically, we removed the variance associated with the number of live births 58 (UK Biobank data field #2734), hormone replacement therapy 7 (#2814), hysterectomy 59 (#3591), bilateral oophorectomy 59 (#2834), body mass index 60 (#21001), diastolic and systolic blood pressure 61 (#4079 and #4080), diabetes 62 (#2443), education 63 (#6138), income 64 (#738), and a composite lifestyle factor 65 . The latter was expressed as a general lifestyle score that was calculated based on a number of factors (see Supplemental Table 4), known to increase / decrease the risk of adverse cardiovascular events.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…7 (#2814), hysterectomy59 (#3591), bilateral oophorectomy 59 (#2834), body mass index60 (#21001), diastolic and systolic 15 blood pressure *…”
mentioning
confidence: 99%